INFLUENCE OF GEOMORPHIC SURFACES ON THE SPATIAL DISTRIBUTION OF SOIL ATTRIBUTES IN A SUGARCANE CULTIVATION AREA - Campos, Milton César Costa (2010)
Variations in soil attributes occur based on relief forms and parent material. The objective of this research was to study the influences of geomorphic surfaces on the spatial distribution of soil attributes in a sugarcane cultivation area. First, 530,67 hectares were mapped by using a Global Positioning System. Then, a Digital Elevation Model was developed and geomorphic surfaces were identified and delimited, according to topographic and stratigraphic criteria based on detailed field investigations. Soil samples were collected every 7 ha, at 0.0-0.25 m and 0.80-1.00 m depths, totalizing 134 samples. Texture, Ca, K, Mg, SB, CEC, V%, pH, and OMS analyses were carried out as well as descriptive statistics and geostatistics analysis. It was concluded that the geostatistic techniques and digital elevation model helped to notice that soil attributes presented limits close to the geomorphic surfaces ones. KEY-WORDS: Soil attributes; geomorphic surface; soil-landscape relationship; landscape form.